The Evolution of UN peacekeeping : case studies and comparative analysis - Durch, William J. (New York, NY : St. Martin's Press, 1993)
United Nations peacekeepers have been sent around the world for nearly five decades to help war-weary people maintain cease-fires, implement force separations, and, most recently, make transitions to democracy. Half of those missions have begun since the end of the Cold War and have helped make the UN headline news. The Evolution of UN Peacekeeping is the first comprehensive post-Cold War assessment of this important tool of conflict containment, its recent, rapid growth and development, the factors that make it work, and the new pressures that place the whole concept at risk. Based on a two-year study for the Ford Foundation by the Henry L. Stimson Center, this book includes between case studies of UN peacekeeping operations from 1947 to 1991 and is suitable for use in courses on international law and organization, regional conflict, conflict management, and cooperative security.
pt. 1. LESSONS LEARNED. -- Getting involved : the political-military context / William J. Durch -- Paying the tab : financial crises -- Running the show : planning and implementation / William J. Durch -- pt. 2. PEACEKEEPING IN THE MEDITERRANEAN AND THE MIDDLE EAST. -- United Nations Special Committee on the Balkans / Karl Th. Birgisson -- United Nations Truce Supervision Organization / Mona Ghali -- United Nations Emergency Force I / Mona Ghali -- United Nations Emergency Force II / Mona Ghali -- United Nations Disengagement Observer Force / Mona Ghali -- United Nations Observation Group in Lebanon / Mona Ghali -- United Nations Interim Force in Lebanon / Mona Ghali -- United Nations Yemen Observation Mission / Karl Th. Birgisson -- United Nations Peacekeeping Force in Cyprus / Karl Th. Birgisson -- United Nations Iran-Iraq Military Observer Group / Brian D. Smith -- The Iraq-Kuwait Observation Mission / William J. Durch -- pt. 3. PEACEKEEPING IN SOUTH AND SOUTHEAST ASIA. -- United Nations Military Observer Group in India and Pakistan / Karl Th. Birgisson -- UN Temporary Executive Authority / William J. Durch -- United Nations Good Offices Mission in Afghanistan and Pakistan / Karl Th. Birgisson -- pt. 4. PEACEKEEPING IN AFRICA. -- The UN Operation in the Congo / William J. Durch -- United Nations Transition Assistance Group in Namibia / Virginia Page Fortna -- United Nations Angola Verification Mission I / Virginia Page Fortna -- United Nations Angola Verification Mission II / Virginia Page Fortna -- United Nations Mission for the Referendum in Western Sahara / William J. Durch -- pt. 5. PEACEKEEPING IN THE WESTERN HEMISPHERE. -- UN Observer Group in Central America / Brian D. Smith and William J. Durch -- Epilogue : Peacekeeping in Uncharted Territory.
Includes bibliographical references (pages 478-500) and index.
Keywords: United Nations -- Peacekeeping forces; United Nations -- Armed Forces; United Nations; United Nations -- Armed Forces; United Nations -- Peacekeeping forces; Peacekeeping forces; Armed Forces; Vredespolitiek; United Nations; International police; Law; United Nations -- Armed Forces